Australian ITE Primary students’ preparedness to teach Arts education: An investigation of perceptions, beliefs and confidence - Bradley Merrick; Dawn Joseph; William Baker (New Zealand Journal of Teachers' Work, 2025)
Preparation of Primary teachers to deliver the Arts in schools continues to receive attention, particularly as the shortage of educators becomes more prevalent. This paper seeks to examine the preparedness of teachers undertaking Initial Teacher Education (ITE) across three Australian Institutions (n=120). The authors explore ‘How does ITE preparation influence teacher confidence, perceived subject value, and readiness to deliver Arts education in primary schools?’  Drawing on responses from an anonymous online survey, descriptive analyses presents the high value placed upon the arts by teachers, while similarly indicating differences between perceptions of preparedness to teach and perceived confidence to teach the Arts. Findings across cohorts are presented, raising issues for future ITE subject design combined with longer term considerations for the sustained integration of the arts.